(untitled) (Italiano LinguaDue, 2020)
Il contributo descrive il progetto “La classe plurilingue. Ricerca sulla complessità linguistica per una didattica inclusiva”, attualmente in corso presso il Dipartimento di Filologia Classica e Italianistica dell’Università di Bologna (2018-2020), presentandone le finalità, la metodologia adottata e i primi risultati raggiunti. Il fine ultimo del progetto è indagare le pratiche del plurilinguismo nella scuola primaria, con un duplice obiettivo: (i) sensibilizzare allievi, genitori e docenti sugli effetti positivi del plurilinguismo, attraverso interventi didattici mirati e attività di formazione sul tema; (ii) fornire ai docenti strumenti di supporto per trasformare la situazione di plurilinguismo in classe in una situazione di arricchimento e crescita culturale per tutti. The multilingual class: neomultiilingualism, self-evaluation and valorization The article describes the project “The multilingual class. Research on linguistic complexity for inclusive teaching”, currently underway at the Department of Classical and Italianistic Philology of the University of Bologna (2018-2020), presenting its aims, the methodology adopted and the initial results. The ultimate aim of the project is to investigate the practices of multilingualism in primary school, with a twofold objective: (i) to make pupils, parents and teachers aware of the positive effects of multilingualism, through targeted educational interventions and training activities on the subject; (ii) to provide teachers with support tools to transform the multilingualism in the classroom into a source of enrichment and cultural growth for all.